A Novel Control Strategy for Air-Cooled Twin-Circuit Screw Chillers. (2015) - Yang, Jia; Chan, K.T.; Dai, Tongyong; Zhang, Hongyu; Zhou, Zhaoguo
Abstract: Air-cooled chillers are generally the major electricity consumers in air-conditioned buildings in the subtropical climate. To improve the energy efficiency of the air-cooled chillers at part load conditions, two or more refrigeration circuits are designed. This paper considers how the use of optimal circuit loading sequence (CLS) enables these chillers to operate more efficiently. A thermodynamic model for the air-cooled chillers with twin refrigeration circuits was developed using TRNSYS and validated using a wide range of operating data. Based on the sophisticated chiller model, an analysis was carried out on how the chiller COP varied with different CLS and variable condensing temperature control (CTC). A chiller plant designed for a representative office building in Hong Kong was investigated to assess the potential electricity savings by use of CLS. 4.2% of the annual electricity consumption by chillers could be achieved with optimal CLS compared with the base case. Under CTC, the coefficient of performance (COP) was improved further, and CTC coupling with optimal CLS would reduce the annual total electricity consumption for cooling by 9.6%.